Micropropagation and total alkaloid extraction of Indian snake root - BAHUGUNA, RAJEEV NAYAN; JOSHI, ROHIT; SINGH, GIRIRAJ; SHUKLA, ALOK; GUPTA, RAMWANT; BAINS, GURDEEP (The Indian Journal of Agricultural Sciences, 2026)
An efficient and reproducible protocol for clonal propagation was developed for Indian snake root (Rauwolfia serpentina L. Benth. ex. Kurtz.) through indirect and direct organogenesis using nodal segment, shoot apices and leaves as explants. For indirect organogenesis using leaf and nodal segments, most efficient callus induction was obtained on MS + 2.0 mg /litre 2, 4-D + 1.0 mg /litre BAP. Proliferated calli further showed highest regeneration response in MS + 1.0 mg / litre BAP + 0.1 mg /litre KIN + 0.1 mg /litre GA3. However, for direct organogenesis using shoot apices and nodal segments, most efficient regeneration was observed in MS +1.0 mg /litre BAP + 0.1 mg /litre KIN + 0.1 mg /litre GA3. For complete removal of contamination due to endophytic microflora, 6.0 g /litre bavistin and 100.0 mg /litre streptomycin was found most effective. Regenerated plantlets obtained both through direct and indirect organogenesis showed multiple shooting on MS + 1.0 mg /litre BAP + 0.1 mg /litre NAA and excellent rooting in MS + 1.0 mg /litre IBA + 1.0 mg /litre IAA. Well rooted plantlets were successfully acclimatized in greenhouse. Plantlets developed through shoot apices showed maximum height, number of shoots and number of leaves. Quantitative estimation of crude alkaloids from six weeks old regenerated plantlets was found similar to that obtained from leaves and stems of one year old field grown plant. The developed protocol can be used for en masse propagation and alkaloid extraction of Rauwolfia serpentina.